Catalytic Hydrogen Production from Methane Partial Oxidation: Mechanism and Kinetic Study - Osman, Ahmed I. (Chemical engineering & technology, 2020)
The multifunctional potential of a transition and noble metal catalyst supported on either a single support or combined oxide support in the catalytic partial oxidation of methane (CPOM) is reviewed. The close interaction and interfacial area between the metal, reducible oxide, and acidic support are highlighted, which are crucial for low‐temperature CPOM. The effects of the catalyst components and their preparation methods are considered. Their impact on the catalytic performance and stability on the CPOM reaction is evaluated. The two main mechanisms of CPOM, namely, direct partial oxidation and combustion and reforming reaction, are also covered along with the most recent kinetic studies. Finally, the deactivation of the CPOM catalysts is evaluated in terms of coke and carbon deposition along with CO poisoning. An overview is given on the multifunctional potential of a transition and noble metal catalyst supported on either single support or combined oxide support in the catalytic partial oxidation of methane. The factors influencing the oxidation reaction along with the mechanism and recent kinetic studies are reported. The deactivation of the catalytic partial oxidation of methane catalysts is evaluated.